Psychological Contracts, Job Stress, and Turnover Intention for Salesperson Retail Company (International Journal of Scientific Research and Management (IJSRM), 2020)
Employees are social beings who have their own backgrounds, personalities and ways of thinking. Employees also often have different ways of dealing with problems, including in terms of handling stress so that the company cannot predict the employee’s attitude. Poor relations between employees and the company can also be an indication of the behavior of employees who move from one company to another. The purpose of this study was to determine the relationship between psychological contracts and work stress with turnover intention. The sample of this study was 274 employees of the sales department of retail companies in Purwokerto. Data were collected using a psychological contract scale, job stress scale, and turnover intention questionnaire. The results showed that there was a significant relationship between psychological contracts with turnover intention (β = -0.276, t = 3.562, p = 0.000). The relationship between job stress and turnover intention also showed a significant relationship (β = 0.213, t = 3.778, p = 0.000).